Clinical presentation of buccal carcinoma. a review of twenty nine patients - Janakarajah, N.; Zain, R.B. (1984)
29 patients with buccal carcinoma were reviewed for the clinical signs and symptoms. The TNM classification following the UICC categories were used for the clinical staging of the lesion. The patient?s race, age, sex and habits were also noted. Most of these patients presented with advanced lesions. The most common signs and symptoms were pain and ulcerations (62%). The histopathology of a well-differentiated squamous cell carcinoma forms a great majority of these lesions (62%). Each of the sign and symptom is discussed in relation to other findings that had been reported.